Celebrating one year anniversary of Contemporary Pediatric Dentistry and introducing the new Congress - Burak Buldur (Arbu Academic Publishing, 2021)
Hi Dear Friends and Colleagues, I am pleased to inform you some of good news regarding the development and process of the Contemporary Pediatric Dentistry (CPD). Since its establishment, CPD has received 80 submissions from all over world within sixteen months, and published 25 articles including review, original research and case reports. CPD has also moved to be indexed in reputed databases. Another achievement was establishment of 1st International Congress of Contemporary Pediatric Dentistry (ICCPD), organized by the CPD, which was taken place on 1- 3 November 2021 as a fully virtual meeting to celebrate the first anniversary of the launch of CPD. The ICCPD hosted 257 registered colleagues from 47 countries. The website of the ICCPD had been viewed more than 5000 visitors from 102 countries in only 2 months. As an exciting action, CPD is now getting ready to initiate the 2nd International Congress of Contemporary Pediatric Dentistry (www.iccpd.org). I feel confident that the ICCPD 2022 will serve as a place of learning where we can all share the latest knowledge and learn the contemporary view, approaches, techniques and treatment options from highly eminent clinicians and/or academicians from different countries. The theme of the ICCPD 2022 is "Contemporary Clinical Techniques in Pediatric Dentistry". The 2nd ICCPD will also host oral and poster presentation. All abstracts will be published in the Supplementary Issue of Contemporary Pediatric Dentistry. It is my honor to invite all colleagues, who have sincere enthusiasm to help children to let them have better oral health, quality of life, smiling and development, to attend 2nd International Congress of Contemporary Pediatric Dentistry to be held on 2-4 September 2022 as a fully virtual meeting. Please follow website and social media accounts of CPD to get latest information regarding Congress and the Journal. Thanks and Best regards, Burak Buldur Editor-in-Chief, CPD Congress President, ICCPD